The feasibility and appropriateness of a peer-to-peer, play-based intervention for improving pragmatic language in children with autism spectrum disorder - Parsons, L.; Cordier, Reinie; Munro, N.; Joosten, Annette (2018)
© 2018, © 2018 The Speech Pathology Association of Australia Limited Published by Informa UK Limited, trading as Taylor & Francis Group. Purpose: This study trialled a play-based, peer-to-peer intervention with children with autism spectrum disorder (ASD) to identify suitable instruments for measuring changes in pragmatic language following the intervention, and evaluate preliminary effectiveness. It also aimed to investigate the appropriateness of the intervention for participants. Method: Ten children with ASD, their typically developing peers, and parents participated. The Pragmatics Observational Measure (POM), Social Emotional Evaluation (SEE) and Profiling Elements of Prosody in Speech Communication (PEPS-C) measured the participant’s social communication skills before, after, and 2-months following the intervention. Parent interviews were conducted two months after the intervention and responses were analysed using a thematic approach. Result: Children demonstrated gains in pragmatic language on the POM (?2(3) = 11.160, p = 0.011) and related higher-level language on the SEE (?2(2) = 6.686, p = 0.035). The PEPS-C did not produce any significant results. Parent interview responses indicated the intervention was appropriate for the children and families involved. Conclusion: The intervention warrants further investigation of effectiveness with a more robust research design. Consideration should be given to using observational measures of pragmatic language away from the clinic environment to evaluate generalisation, and future development of the intervention might consider variations in playmates and group size.